2011
DOI: 10.1175/2010jcli3850.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Climate Change on Air Quality–Related Meteorological Conditions in California. Part II: Present versus Future Time Simulation Analysis

Abstract: In this study, the Weather Research and Forecasting (WRF) model was applied to dynamically downscale the Parallel Climate Model (PCM) projection for the climate change impact on regional meteorological conditions in California. Comparisons were made for meteorological fields that strongly influence regional air quality between the current (2000-06) and future (2047-53) downscaling results to infer potential air pollution changes in California. Changes in both the meteorological fields and the implied future ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
3
10
1
Order By: Relevance
“…Except in August, EXP always provided slightly higher 10m wind speeds than CON. This general overestimation of 10m wind speed agrees with results from previous studies on WRF's performance in reproducing inversions and/or the wind field under stagnant or calm wind conditions [19] [73] [74].…”
Section: Windsupporting
confidence: 89%
See 1 more Smart Citation
“…Except in August, EXP always provided slightly higher 10m wind speeds than CON. This general overestimation of 10m wind speed agrees with results from previous studies on WRF's performance in reproducing inversions and/or the wind field under stagnant or calm wind conditions [19] [73] [74].…”
Section: Windsupporting
confidence: 89%
“…Since the analysis data based on observations small-scale impacts of roughness were indirectly included to a certain degree despite of the relatively coarse resolution. The low data density explains some of the systematic differences found in this and many other studies between simulated and observed wind fields [74] [77].…”
Section: Windcontrasting
confidence: 63%
“…4a) suggests that these two sets of simulations predict dissimilar land-sea breezes. More details of landsea breeze in CA and its future changes will be explored in Part II of the study (Zhao et al 2011). During winter, PCM WRF simulations underestimated T2 for almost the entire analysis domain, except for over the Pacific Ocean adjacent to Southern CA and Mexico.…”
Section: Downscaling Results Analysismentioning
confidence: 99%
“…This phenomenon was studied and the possible reasons were explored. Part II of this study, which is presented in a separate paper (Zhao et al 2011), compares present and future simulations driven by PCM data to evaluate the impacts of climate change on meteorological conditions related to air quality, including land-sea breeze, in CA.…”
Section: Introductionmentioning
confidence: 99%
“…Of the total PM 2.5 mass, primary PM concentrations were only under-estimated by 12-66% while secondary PM concentrations were under-estimated by ∼18-73%. The majority of this under-prediction is likely caused by the excess ventilation produced by the PCM-WRF meteorological predictions that should be consistent in both present and future climate so that a minimum amount of net bias is introduced into the comparison (Zhao et al, 2010a). The present study is among the first to evaluate climate-air quality model performance over a climatologically relevant time-frame (7-year averages) using prognostic meteorology produced by a GCM.…”
Section: Discussionmentioning
confidence: 99%